The Presence of the Prophet in Early Modern and Contemporary Islam Volume 1, The Prophet Between Doctrine, Literature and Arts: Historical Legacies and Their Unfolding - Gril, Denis; Reichmuth, Stefan; Sarmis, Dilek (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2022)
This collective volume explores the figure of the Prophet Muhammad in early Islam and its pious transformations in later times. It illuminates the interplay of doctrine, literature and visual arts in the formation of a "Prophetic culture".; Readership: Scientific and general readership interested in Islam and Muslim culture in different regional and historical contexts, Historical Anthropology of Religion, Comparative Religion, Religious Literature and Arts.